Evaluating the prescribing and management practices of venlafaxine at a public sector psychiatric hospital - Naidu, Bavika (Rhodes University, Faculty of Pharmacy, Pharmacy)
Neuropsychiatric conditions have been ranked third in South Africa according to some of the most recent reviews of disease burden, following human immunodeficiency virus/acquired immune deficiency syndrome and other infectious diseases (Bateman, 2012:70; South African Depression and Anxiety Group, 2018). For depressive disorders, the conventional selective serotonin reuptake inhibitors (e.g. fluoxetine), are common first-step treatments due to their relatively low toxicity and high tolerability (Rush et al., 2006:1231). The class of selective noradrenaline reuptake inhibitors (e.g. venlafaxine) is relatively new on the market. The first SNRI to be marketed in the United States was venlafaxine immediate-release (IR). It was approved by the United States FDA in 1993 (Sansone and Sansone, 2014:37) and was soon followed by the introduction of a micro-encapsulated extended-release (XR) formulation in 1997. Currently there is no published or readily available information concerning the prescribing and management patterns of venlafaxine as well as the incidence and types of adverse effects experienced by patients in the public health sector of South Africa besides the established increased in blood pressure.
Keywords: Venlafaxine; Anxiety disorcers -- Treatment; Depression, Mental -- Treatment